Urgensi Pengaturan Perkara Constitutional Complaint Dalam Kewenangan Mahkamah Konstitusi - Rahmat Muhajir Nugroho (Universitas Ahmad Dahlan, 2016)
ABSTRACTThis study aimed to evaluate the mechanism for settling disputes in the Constitutional Court containing elements of constitutional complaint. In particular, this study focused on two things: first assessing the urgency/ importance of the idea of setting constitutional complaint in the Constitutional Court's authority. Secondly, to formulate recommendations on setting constitutional complaint in the Constitutional Court's authority.The method used in this research is descriptive qualitative. This type of research is a doctrinal law. This research studied the concept and implementation of the judicial settlement of cases that contain elements of constitutional complaint (complaint constitution) by the Constitutional Court.The conclusion of this study is an important constitutional complaint mechanism is contained within the competence of the Constitutional Court to solve problems of injustice experienced by citizens as a result of public policies undertaken by the government in a broad sense, namely the executive, legislature and judiciary. Setting constitutional complaint within the competence of the Constitutional Court does not have to be explicitly stipulated in the constitution, but enough in the explanation of the Constitutional Court Act. That is not to add direct authority of the Court, but expand the meaning of the authority of the Court in testing the law.